The impact of variation evaluation practices in teaching from one professor to another due to the difference in academic qualifications among physical education and sports professors in secondary education in algeria - Yechekour Abdenour; Zemour Abdelkader (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
The purpose of this study was to investigate the impact of the difference in évaluation practices in teaching from one teacher to another, depending on the scientific qualification of physical education and sports teachers in secondary education in Algeria. For this purpose, we relied on the descriptive-analytical approach, in which we distributed a questionnaire on assessment practices in teaching to a research sample of 416 physical education and sports teachers in the secondary stage who were selected randomly. After collecting the results and processing them statistically, it was found that the assessment practices in teaching among physical education and sports teachers in secondary education in Algeria differ from one teacher to another depending on the variable of scientific qualification. Consequently, the study recommended the need for qualitative and comprehensive training for physical education and sports teachers in the field of modern assessment and its strategies.